A comparison of influences on the landscape of two social-ecological systems. (30th November 2016) - Sharma, Divya; Holmes, Ignacia; Vergara-Asenjo, Gerardo; Miller, William N.; Cunampio, Mitzy; B. Cunampio, Raquel; B. Cunampio, Mara; Potvin, Catherine
Highlights: Ostrom's social-ecological systems framework diagnosed two disparate landscapes. Resource System topography and Actor socioeconomics led to divergent forest cover. Historical land endowment (inherited Resource Unit quality) shapes current land use. Local leaders and institutions (Governance) conserve forest via external resources. Abstract: Case studies of social-ecological landscapes that consider local, spatially explicit land cover changes are necessary for the development of generalised knowledge on deforestation. This study focussed on two indigenous territories of eastern Panama that share the same settlement history, size and location but are perceived by local dwellers to differ in terms of land cover. By considering the territories social-ecological systems made up of Resource Systems, Resource Units, Actors and Governance Structures, following Ostrom's framework for analysing the sustainability of social-ecological systems (McGinnis and Ostrom, 2014), we sought to determine which social-ecological factors could have led to divergent land cover outcomes to address local leaders' concerns and inform future land management strategies. We conducted quantitative, spatial analysis using ArcGIS and multivariate statistics from numerical ecology on land cover data from participatory maps, and household level socio-economic data from semi-structured interviews and surveys. Results illustrate that the Resource System's topography and Actors' socioeconomics, namely number of people at home and household land ownership, are constraining variables on land cover and help explain divergent forest cover. To reconstruct the influence of history and Governance Structure on the landscapes, we conducted qualitative data collection, namely participatory pebble scoring of historical land cover, interviews with key informants, an archival search, and creation of a participatory historical timeline. Historical governmental timber extraction in the region pre-settlement, guided by topography constraints, may have led to degraded Resource Units (forests) susceptible to clearing. The Governance Structure's self-organizing, monitoring and networking activities with outside institutions in scientific projects, enabled by Actors' leadership and social capital, likely encouraged forest conservation in the forest-rich territory. Future land management could therefore benefit from establishment of a local non-governmental organisation to coordinate a communal vision of management and harness external conservation resources. Our findings suggest that inputting both qualitative and quantitative data obtained by participatory methods into Ostrom's framework can help diagnose territories with divergent landscapes, and thereby inform both forest conservation science and local land management.